Framing technology society, choice and change - Green, Lelia 1956-; Guinery, Roger (Routledge, 2023)
Framing Technology uses an interdisciplinary approach to explore some of the key issues in technology today, including virtual reality, gender, health, the environment, regulation, the information society, surveillance and globalisation.
"Ebook published 8 May 2023" -- publisher's website. - Includes bibliographical references and index. - Description based on online resource; title from digital title page (viewed on June 12, 2023)
Keywords: Technology -- Social aspects; Technological innovations -- Social aspects; Social change; Innovations; Aspect social; SOCIAL SCIENCE / Media Studies; Technological innovations; Social aspects; Technology; Social aspects